The influence of the Human Development Index (HDI), GDP Per Capita and Open Unemployment Rate to Poverty in Regencies/Cities of Aceh Province in 2017 – 2022 - Albani, Muhammad Iqbal; Hutapia, Hutapia (Asian Journal of Management Analytics, 2025)
This study aims to analyze the effect of Human Development Index (HDI), Gross Regional Domestic Product (GRDP) per capita, and Open Unemployment Rate (TPT) on poverty in Regencies/Cities in Aceh Province in the period 2017-2022. The data used are panel data from 23 regencies/cities in Aceh obtained from the Central Statistics Agency (BPS). The analysis method used is panel data regression with the Fixed Effect Model (FEM). The results of the study show that HDI has a negative and significant effect on poverty, while GRDP per capita has a significant positive effect. TPT also does not show a significant effect on poverty. Overall, these variables explain 98% of the variation in poverty in Aceh, HDI is the main factor influencing poverty reduction with a coefficient value of -0.99182. This study suggests that local governments focus on improving the quality of human resources to reduce poverty in Aceh.